Conservation in the internet age : (Island Press, 2002)
Conservation in the Internet Age offers an innovative, cross-disciplinary perspective on critical changes on the land and in the field of conservation. The book: provides a general overview of the impact of new technologies and networks, explores the potentially disruptive impacts of the new networks on open space and biodiversity, explores the potentially disruptive impacts of the new networks on open space and biodiversity, considers how rapid change in the Internet Age offers the potential for landmark conservation initiatives.